TyrR, the regulator of aromatic amino acid metabolism, is required for mice infection of Yersinia pestis - Deng, Zhongliang; Liu, Zizhong; He, Junming; Wang, Jing; Yan, Yanfeng; Wang, Xiaoyi; Cui, Yujun; Bi, Yujing; Du, Zongmin; Song, Yajun; Yang, Ruifu; Han, Yanping (Frontiers in Microbiology, 2015)
Yersinia pestis, the causative agent of plague, poses a serious health threat to rodents and human beings. TyrR is a transcriptional regulator that controls the metabolism of aromatic amino acids in Escherichia coli. In this paper, TyrR played an important role in Y. pestis virulence. Inactivation of tyrR did not seem to affect the in vitro growth of this organism, but resulted in at least 10,000-fold attenuation compared with the wild-type (WT) strain upon subcutaneous infection to mice. In addition, loads of tyrR mutant within mice livers and spleens significantly decreased compared with the WT strain. Transcriptome analysis revealed that TyrR, directly or indirectly, regulated 29 genes encoded on Y. pestis chromosome or plasmids under in vitro growth condition. Similar to the regulatory function of this protein in E. coli, five aromatic-pathway genes (aroF-tyrA, aroP, aroL, and tyrP) were significantly reduced upon deletion of the tyrR gene. Two genes (glnL and glnG) that encode sensory histidine kinase and regulator in a two-component regulatory system involved in nitrogen assimilation were downregulated in the tyrR mutant. Several genes encoding type III secretion proteins were transcribed by 2.0- to 4.2-fold in a tyrR mutant relative to the WT strain. Interestingly, the acid-stressed genes, hdeB and hdeD, were downregulated, and such downregulation partly accounted for the decrease in tolerance of the tyrR mutant under acidic conditions. In conclusion, regulation of TyrR in Y. pestis is similar to, but distinct from, that in E. coli. TyrR is a metabolic virulence determinant in Y. pestis that is important for extracellular survival and/or proliferation.